2021
DOI: 10.1155/2021/1552127
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Ameliorates White Matter Injury after Ischemic Stroke by Inhibiting Microglia/Macrophage Pyroptosis through NF‐κB Suppression and NLRP3 Inflammasome Inhibition

Abstract: NLRP3 inflammasome-mediated pyroptosis is a proinflammatory programmed cell death pathway, which plays a vital role in functional outcomes after stroke. We previously described the beneficial effects of curcumin against stroke-induced neuronal damage through modulating microglial polarization. However, the impact of curcumin on microglial pyroptosis remains unknown. Here, stroke was modeled in mice by middle cerebral artery occlusion (MCAO) for 60 minutes and treated with curcumin (150 mg/kg) intraperitoneally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 53 publications
3
89
0
Order By: Relevance
“…Microglia are crucial mediators of neuroinflammation and the immune response following central nervous system (CNS) injury [ 26 , 27 ], and are also regarded as the main cell type in which pyroptosis occurs in the CNS [ 9 , 23 , 28 ]. Momentously, NLRP3 inflammasome-mediated GSDMD-triggered pyroptosis in microglia has been implicated in the pathogenesis of subarachnoid hemorrhage [ 29 ], cerebral ischemia/reperfusion injury [ 30 , 31 ] and spinal cord injury [ 23 ]. Although microglia pyroptosis is repeatedly delineated in distinct neuroinflammatory-related diseases, the underlying mechanism of this process remains to be fully elucidated in CVST.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia are crucial mediators of neuroinflammation and the immune response following central nervous system (CNS) injury [ 26 , 27 ], and are also regarded as the main cell type in which pyroptosis occurs in the CNS [ 9 , 23 , 28 ]. Momentously, NLRP3 inflammasome-mediated GSDMD-triggered pyroptosis in microglia has been implicated in the pathogenesis of subarachnoid hemorrhage [ 29 ], cerebral ischemia/reperfusion injury [ 30 , 31 ] and spinal cord injury [ 23 ]. Although microglia pyroptosis is repeatedly delineated in distinct neuroinflammatory-related diseases, the underlying mechanism of this process remains to be fully elucidated in CVST.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia play a dual role in ischemic brain injury (Ran et al, 2021 ). On the one hand, after cerebral ischemia, microglia respond rapidly to the microenvironment of the brain (Dong et al, 2021 ), change from a resting state (“branching” with pruning synaptic function) to an activated state (“amoeba” with phagocytic function), and migrate to the ischemic region to protect neurons by forming phagocytic fragments (Shi and Pamer, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, attention has recently been paid to the important effect that curcumin can have on the pyroptosis process linked with microglial activation. In a recent study, in fact it was demonstrated that curcumin treatment can attenuate microglial pyroptosis improving white matter integrity as well as functional outcomes, through NF-κB signaling suppression and subsequent NLRP3 inflammasome inhibition in an in vivo model of ischemic stroke pointing out that curcumin has a direct important inhibitory effect on microglial inflammasome activation and pyroptosis [150]. Moreover, in another recent study it was reported that curcumin treatment is protective against cognitive impairments in a rat model of chronic cerebral hypoperfusion combined with diabetes mellitus by suppressing neuroinflammation, apoptosis, and pyroptosis via the regulation of the TREM2/TLR-4/NF-κB pathway in microglia [151].…”
Section: Neuroprotective Effect Of Curcumin In Vivo Studiesmentioning
confidence: 99%